2020
DOI: 10.3390/w12020598
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soil Iron on the Estimation of Soil Water Content Using Dielectric Sensors

Abstract: Nowadays, the estimation of volumetric soil water content (θ) through apparent dielectric permittivity (εa) is the most widely used method. The purpose of this study is to investigate the effect of the high iron content of two sandy loam soils on estimating their water content using two dielectric sensors. These sensors are the WET sensor operating at 20 MHz and the ML2 sensor operating at 100 MHz. Experiments on specific soil columns, in the laboratory, by mixing different amounts of water in the soils to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Gravimetric measurements of soil water content can also give some indications of water availability for plants and can in some conditions be the only method practically feasible. Sensors measuring soil moisture frequently overestimate soil humidity in soils with high levels of iron [ 113 ] and in this case, water content can be measured gravimetrically.…”
Section: Environmental Variablesmentioning
confidence: 99%
“…Gravimetric measurements of soil water content can also give some indications of water availability for plants and can in some conditions be the only method practically feasible. Sensors measuring soil moisture frequently overestimate soil humidity in soils with high levels of iron [ 113 ] and in this case, water content can be measured gravimetrically.…”
Section: Environmental Variablesmentioning
confidence: 99%
“…The probe calibration is always necessary, but it is particularly important for capacitance probes working at low frequency, especially when used in a medium having high iron content. The iron content affects the imaginary component (ε") of the dielectric constant of the soil/water system [55]. For these soils, the difference between actual and estimated values by the manufacturer parameters tends to increase as the degree of saturation of soil increases.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Robinson et al [57], the iron oxide content, coupled with the length of sensor rods used, play an important role in capacitance probe working at 100 MHz, such as the PR2/6 probe. However, recent research has shown that the effects of iron content are more evident for instruments working at even lower frequencies (cf., a WET sensor working at 50 MHz, [55]). The effects of an accurate calibration are also evident when analyzing the temporal variations of soil water content with depth in the experimental field.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to their relatively low operating frequency, capacitance sensors are susceptible to secondary effects (e.g., induced by strong variations in soil temperature and salinity-induced electrical conductivity) that affect their measurement accuracy and precision [8][9][10][11][12][13][14][15][16]. Therefore, proper calibration is mandatory to reliably convert the soil dielectric permittivity into soil water content, especially for fine-textured soils [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%